Intersectional pedagogy : Complicating identity and social justice - Case, Kim A. (Routledge, 2017)
Intersectional Pedagogy explores best practices for effective teaching and learning about intersections of identity as informed by intersectional theory. Formatted in three easy-to-follow sections, this collection explores the pedagogy of intersectionality to address lived experiences that result from privileged and oppressed identities. After an initial overview of intersectional foundations and theory, the collection offers classroom strategies and approaches for teaching and learning about intersectionality and social justice. With contributions from scholars in education, psychology, sociology and women’s studies, Intersectional Pedagogy include a range of disciplinary perspectives and evidence-based pedagogy.
Keywords: approches et analyses; discipline; formations; féminisme décolonial; identités; intersectionnalité; justice sociale; outils; ouvrages de références; psychologie; pédagogie; ressource en ligne; sciences de l'éducation; sciences humaines; sociologie; thématiques; études de genres

Deconstructing privilege: Teaching and learning as allies in the classroom - Case, Kim (Routledge, 2013)
Although scholarly examinations of privilege have increased in recent decades, an emphasis on privilege studies pedagogy remains lacking within institutions. This edited collection explores best practices for effective teaching and learning about various forms of systemic group privilege such as that based on race, gender, sexuality, religion, and class. Formatted in three easy-to-follow sections, Deconstructing Privilege charts the history of privilege studies and provides intersectional approaches to the topic. Drawing on a wealth of research and real-life accounts, this book gives educators both the theoretical foundations they need to address issues of privilege in the classroom and practical ways to forge new paths for critical dialogues in educational settings. Combining interdisciplinary contributions from leading experts in the field– such as Tim Wise and Abby Ferber– with pedagogical strategies and tips for teaching about privilege, Deconstructing Privilege is an essential book for any educator who wants to address what privilege really means in the classroom.
Keywords: amériques; approches et analyses; discipline; intersectionnalité; inégalités; justice sociale; outils; ouvrages de références; privilèges; régions géographiques; sciences de l'éducation; systèmes d'oppressions; états-unis